New class of lead free perovskite material for low-cost solar cell application - Rahul, -; Singh, Pramod Kumar; Singh, Rahul; Singh, Vijay; Bhattacharya, Bhaskar; Khan, Zishan H. (Elsevier, 2018)
In this paper, we fabricate a new class of perovskite sensitizer material for photovoltaic application. This is not only low-cost perovskite material but also is a non-toxic material for solar cell as compared to the conventional materials used in PSC. Detailed procedure of synthesis of CH 3 NH 3 SnCl 3 material and its application in fabrication of PSC is presented in the article. Perovskite material i.e. methyl ammonium tin tri-chloride (CH 3 NH 3 SnCl 3 ) was prepared by direct deposition of equimolar concentration of CH 3 NH 3 Cl and tin chloride (SnCl 2 ) in dimethylformamide (DMF) solution. X-ray diffraction pattern (XRD) of the material confirms the formation of perovskite structure whereas, UV–vis absorption spectroscopy shows the absorption range of these material. Crystal formation of the perovskite is confirmed from the scanning electron microscope (SEM). A comparison of the crystal and powder form of perovskite material is discussed in depth in terms of structural, optical and electrical properties.